Comparative analysis of synchronous motors - Sarac, Vasilija (JET on-line, 2021)
This paper compares the parameters, steady-state and transient characteristics of two different types of synchronous motors (SM) – a motor with surface mounted magnets on the rotor, and a motor with embedded magnets and squirrel cage winding, widely known as a line-start synchronous motor. The comparison is based on results obtained from analytical, numerical and transient models of both motors for the same output power of the motors. The models for obtaining transient characteristics allow comparison of acceleration of both motors taking into consideration that the line-start SM is a self-starting motor while the SM with surface magnets is always started with the aid of a PWM inverter. The results obtained from the analytical, numerical and transient models of the motors should assist in choosing the most cost-effective solution in terms of the type of the motor for the appropriate application.
Keywords: FEM models; karakteristike stabilnega stanja; Modeli FEM; prehodne značilnosti; sinhroni motorji; steady-state characteristics; synchronous motors; transient characteristics